Profitabilitas Ditinjau Menggunakan Struktur Modal, Pertumbuhan Perusahaan, Modal Kerja dan Penjualan Bersih - Della Puspita; Nera Marinda Machdar (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses capital structure, company growth, working capital and net sales on profitability listed on the IDX. In the context of increasingly fierce business competition, companies are required to increase revenue and manage resources well to achieve an optimal level of profitability. The purpose of this study is to find and analyze theories that mention the effect of capital structure, company growth, working capital and net sales on profitability. This research uses the literature review method. In this study, researchers present the reasons for other explanatory variables, as well as findings from previous literature. The theories behind this research are agency theory, exchange theory and signal theory. The mapping of other explanatory variables that suggest profitability consists of capital structure, Company growth, working capital and net sales. The results suggest that there are different relationships between capital structure, corporate growth, working capital and net sales on profitability and thus no consensus has been reached. This study provides a detailed illustration based on reality and can help future research using capital structure, firm growth, working capital and net sales on profitability.